Pricing of Deposit Insurance - Laeven, Luc (World Bank, Washington, DC, 2014)
The author aims to provide guidelines for the pricing of deposit insurance in different countries. He presents several methodologies that can be used to set benchmarks for the pricing level of deposit insurance in a country, and quantifies how specific design features affect the cost of deposit insurance. The author makes several contributions to our understanding of what drives the price of deposit insurance. For example, he shows how risk diversification and risk differentiation within a deposit insurance system can reduce the price of deposit insurance. The author also finds that deposit insurance is under-priced in many countries around the world, notably in several developing countries. More important, his estimates suggest that many countries cannot afford deposit insurance. Deposit insurance is unlikely to be a viable option in a country with weak banks and institutions. The author does not recommend a funded deposit insurance scheme, but rather he argues that for countries that have adopted or are adopting deposit insurance and have decided to pre-fund it, pricing it as accurately as possible is important.